Development Of Problem-Based Learning Device On Matrix Material For Class X Smk Kesehatan Imelda Rantauprapat - Amin Harahap (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study aims to produce a good problem-based learning tools and describe the effectiveness of problem-based learning in matrix material for Class X SMK Rantauprapat. This research development follows the design of 4-D model from Thiagarajan (1974) to the 3-D stage only: the definition stage, the design stage, and the development stage of the device. The learning tools developed are learning implementation plan (RPP), student worksheet (LKS), Learning Outcome Test (THB). Instruments used in this study, namely the validation sheet of learning devices, student activity observation sheet, observation sheet teacher's ability to manage learning, and student response questionnaire. Class trials conducted in Class X-D SMK Health Imelda Rantauprapat obtained the results of a device consisting of: learning device is said to be valid by the validator, the ability of teachers to manage learning is good on average (4.52), good student activity, student response to positive learning, learning outcomes test valid, reliability is (0.59), and sensitive items between 0 and 1, assessment of good attitudes. For class effectiveness test conducted in Class X-MM SMK Health Imelda Rantauprapat who have met the requirements of effectiveness, namely: completeness of learning classically fulfilled (85%), good student activity, student response to positive learning, and the ability of teachers to meet the criteria of good average (4.28)